Pengaruh Penerapan Model Pembelajaran Collaborative Problem Solving terhadap Kreativitas Peserta Didik pada Mata Pelajaran Matematika Kelas V - Putri, Yusti Sahida; Sasmita, Febriarsita Eka; Alifyah, Hanik Yuni (Lembaga Yasin AlSys, 2024)
This study aims to determine the influence of the Collaborative Problem Solving (CPS) learning model on students' creativity, which is needed in the 21st Century, in Mathematics learning subjects in grade V including block and cube spaces. The study used a quantitative method with a quasi-experimental design with a pretest-posttest control group design. with Class V-A (CPS Class) and Class 5B (Conventional Class) samples. The results of the calculation from this study show that the Collaborative Problem Solving learning model using the N-Gain Test shows an increase in creativity in the CPS group getting an average score of 75.6151% including the